Interaction of stattic, A STAT3 inhibitor with human serum albumin: Spectroscopic and computational study / Ida Syazwani Mohd Affandi - Ida Syazwani , Mohd Affandi (2017)
Interaction of stattic (ST), an inhibitor of signal transducer and activation of transcription 3, STAT3 with human serum albumin (HSA), the major transport protein in human blood circulation was investigated using several spectroscopic techniques and molecular docking method. Moderate binding affinity (Ka = 2.60−1.45  104 M−1) between ST and HSA was revealed from the analysis of the fluorescence quenching titration data at three different temperatures. A decreasing trend of the binding constant with increasing temperature suggested involvement of the static quenching mechanism, thus pointing towards the formation of ST-HSA complex. The complex was supposed to be stabilized by hydrophobic interactions and hydrogen bonds, as indicated by the thermodynamic data (ΔH = −14.9 kJ mol−1 and ΔS = +32.8 J mol−1 K−1). The far-UV and the near-UV CD spectral results showed slight alteration in the secondary and the tertiary structures of HSA upon ST binding. Whereas ST binding to HSA induced microenvironmental perturbation around protein’s aromatic fluorophores, as evident from the three-dimensional fluorescence spectra, it increased protein’s thermal stability. Competitive ligand displacement along with molecular docking results suggested Sudlow's site I of HSA as the ST binding site. A comparison of ST binding characteristics of serum albumins for bovine (BSA), porcine (PSA), sheep (SSA) and rabbit (RbSA) showed similarity between HSA and PSA in terms of binding affinity and between HSA and BSA based on warfarin displacement results. Further studies are needed to clarify which of these proteins (PSA or BSA) match closely to HSA in order to be used as a suitable animal model for pharmacological studies.